Peran dan Tantangan Penggunaan E-Learning sebagai Pendukung Proses Pembelajaran di Perguruan Tinggi: Sebuah Tinjauan Literatur - Arika, Siti (Cognoscere: Jurnal Komunikasi dan Media Pendidikan, 2023)
The use of E-Learning as a support for the learning process in higher education has become a significant research focus. This article employs a literature review method to analyze the benefits of E-Learning, the various formats of learning that can be delivered, online collaboration and discussion, as well as the challenges that may arise in its implementation. Based on the findings from the literature, the use of E-Learning enhances the accessibility of learning in higher education, provides customizable learning formats to cater to students' learning styles, and facilitates interaction and collaboration between students and instructors. However, challenges such as limited internet access and the paradigm shift in teaching need to be addressed. This article provides recommendations to improve infrastructure, train instructors, meet students' needs, and overcome challenges. With appropriate implementation, E-Learning can have a positive impact on higher education. Keywords: E-Learning, higher education, accessibility, learning formats, online collaboration. Abstrak Penggunaan E-Learning sebagai pendukung proses pembelajaran di perguruan tinggi telah menjadi fokus penelitian yang signifikan. Artikel ini menggunakan metode riset literatur untuk menganalisis manfaat penggunaan E-Learning, format pembelajaran yang dapat disajikan, kolaborasi dan diskusi daring, serta tantangan yang mungkin muncul dalam implementasinya. Berdasarkan temuan literatur, penggunaan E-Learning meningkatkan aksesibilitas pembelajaran di perguruan tinggi, memberikan format pembelajaran yang dapat disesuaikan dengan gaya belajar mahasiswa, dan memfasilitasi interaksi dan kolaborasi antara mahasiswa dan dosen. Namun, tantangan seperti keterbatasan akses internet dan perubahan paradigma pengajaran perlu diatasi. Artikel ini memberikan saran untuk meningkatkan infrastruktur, pelatihan dosen, mendukung kebutuhan mahasiswa, dan mengatasi tantangan yang muncul. Dengan implementasi yang tepat, penggunaan E-Learning dapat memberikan dampak positif dalam pendidikan tinggi.